Assessment of Long Distance Supply of Tomato in Gujarat Province, India - Vala, K. V.; Kumpavat, M. T.; Dutta , S. (Research Highlights in Agricultural Sciences Vol. 1, 2022)
One of the most significant and well-liked vegetables in the world is the tomato. India is the world's second-largest producer of tomatoes. Due to growing demand, rising consumption, and higher rates of return, tomato output has been steadily rising over the past 15 years. One of the most important commodities on the Indian market is the tomato, which is consumed both raw and processed. Therefore, this delicious produce is required throughout the nation. Huge quantities of tomatoes are moved yearly from the production area to various locations. Additionally, tomato is being carried from Anand to various regions of India. Therefore present study was taken up to assess the various post-harvest handling steps involved in tomato supply, its losses and economics of supply. Traders and persons involved are not trained, also not aware of physiology of tomato fruit, resulting in poor handling and loss. Losses during sorting observed to be 8-10%, whereas physical loss in weight observed 2-3% during transport. Lack of suitable handling, collection, and packing house facilities affects the tomato supply chain. Growers do not benefit; instead, middlemen and merchants get more. Merchants gets profit of Rs 4- 7 per kg of selling at end place. There is overall requirement of scientific intervention at each stage in the supply chain.